Intraocular iron injection induces oxidative stress followed by elements of geographic atrophy and sympathetic ophthalmia. Issue 11 (9th October 2021) - Liu, Yingrui; Bell, Brent A.; Song, Ying; Kim, Hye J.; Sterling, Jacob K.; Kim, Benjamin J.; Poli, Maura; Guo, Michelle; Zhang, Kevin; Rao, Aditya; Sparrow, Janet R.; Su, Guanfang; et al.
Abstract: Iron has been implicated in the pathogenesis of age‐related retinal diseases, including age‐related macular degeneration (AMD). Previous work showed that intravitreal (IVT) injection of iron induces acute photoreceptor death, lipid peroxidation, and autofluorescence (AF). Herein, we extend this work, finding surprising chronic features of the model: geographic atrophy and sympathetic ophthalmia. We provide new mechanistic insights derived from focal AF in the photoreceptors, quantification of bisretinoids, and localization of carboxyethyl pyrrole, an oxidized adduct of docosahexaenoic acid associated with AMD. In mice given IVT ferric ammonium citrate (FAC), RPE died in patches that slowly expanded at their borders, like human geographic atrophy. There was green AF in the photoreceptor ellipsoid, a mitochondria‐rich region, 4 h after injection, followed later by gold AF in rod outer segments, RPE and subretinal myeloid cells. The green AF signature is consistent with flavin adenine dinucleotide, while measured increases in the bisretinoid all‐ trans ‐retinal dimer are consistent with the gold AF. FAC induced formation carboxyethyl pyrrole accumulation first in photoreceptors, then in RPE and myeloid cells. Quantitative PCR on neural retina and RPE indicated antioxidant upregulation and inflammation. Unexpectedly, reminiscent of sympathetic ophthalmia, autofluorescent myeloid cells containing abundant iron infiltrated the saline‐injected fellow eyes only if the contralateral eye had received IVT FAC. These findings provide mechanistic insights into the potential toxicity caused by AMD‐associated retinal iron accumulation. The mouse model will be useful for testing antioxidants, iron chelators, ferroptosis inhibitors, anti‐inflammatory medications, and choroidal neovascularization inhibitors. Abstract : Intravitreal injection of iron induces photoreceptor oxidative stress, resulting in increased autofluorescence, lipid peroxidation, and myeloid cell infiltration associated with retinal degeneration, geographic atrophy, and choroidal neovascularization.